2001
DOI: 10.1161/hs1201.099803
|View full text |Cite
|
Sign up to set email alerts
|

Report of the Substudy Assessing the Impact of Neurocognitive Function on Quality of Life 5 Years After Cardiac Surgery

Abstract: Background and Purpose-The importance of perioperative cognitive decline has long been debated. We recently demonstrated a significant correlation between perioperative cognitive decline and long-term cognitive dysfunction. Despite this association, some still question the importance of these changes in cognitive function to the quality of life of patients and their families. The purpose of our investigation was to determine the association between cognitive dysfunction and long-term quality of life after card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
200
2
15

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 327 publications
(221 citation statements)
references
References 35 publications
4
200
2
15
Order By: Relevance
“…35 While, neurocognitive functioning 5 years after coronary artery bypass grafting (CABG), is found to have a strong connection with decreased HRQoL. 36 There are a number of papers that study HRQoL in stroke. Their findings suggest that factors such as hemispheral localization of the lesion, paresis, coordination disturbances and especially subjective tendency to depression are highly correlated with poor HRQoL.…”
mentioning
confidence: 99%
“…35 While, neurocognitive functioning 5 years after coronary artery bypass grafting (CABG), is found to have a strong connection with decreased HRQoL. 36 There are a number of papers that study HRQoL in stroke. Their findings suggest that factors such as hemispheral localization of the lesion, paresis, coordination disturbances and especially subjective tendency to depression are highly correlated with poor HRQoL.…”
mentioning
confidence: 99%
“…18,24 Similarly to noncardiac surgery, it has been shown that patients with POCD had poorer quality of life when assessed at one year and five years after otherwise successful cardiac surgery. 25,26 Lower five-year overall cognitive function scores were associated with lower general health and a less productive working status. These findings have significant social and financial implications.…”
Section: Discussionmentioning
confidence: 98%
“…3,4 The mechanism(s) of POCD remains elusive, although several contributing factors have been proposed, 1 including the exacerbation of preoperative cognitive impairment, 5 genetic predisposition, cerebral embolism/hypoperfusion, hemodilution, hyperglycemia, anesthetic neurotoxicity, [6][7][8] and perioperative hyperthermia. 9 In addition to these mechanisms, cerebral inflammation in response to embolic and other events during CPB, manifested by transcerebral platelet activation, 10 has also been proposed as a mechanism linking POCD to cardiac surgery.…”
Section: Résumémentioning
confidence: 99%